“A Fuzzy Decision Framework for Analysis of Accidental Black Spot” - Snehal U Bobade, Ravindra K Lad (Mathematical Statistician and Engineering Applications, 2023)
The economic development of any country is directly and strongly related to transportation system and the main aim of transportation systemis to provide safe and efficient movement of fright and human from one place to another place. In transportation system traffic safety is more essential phenomenon and it is affected by numerous factors such as Structural defect and road condition. Prediction of road accidents plays very important role in human life and road safety. A Road accident causes a major problemon health and wealth of human being.Road safety is not measure by single parameter it involves an opinions of various decision makers involved in the decision processes.Multicriteria Decision Making (MCDM) in the decision process improves the quality of the decision especially for those which problems contain multiple criteria. This paper consists of systematic procedure based on fuzzy set theory to evaluate accidental black spot severity indexand based on that index ranking of particular spot was done. Study aim to minimize road accidents by developing Multi Criteria Decision Making Model (MCDM) which consist of perception of experts’ based on linguistic terms for the criteria road conditions and structural defects which are further classified in various parameters (parameters was selected based on IRC), relationship among the decision criteria, and finding out factor which is responsible for occurrence of accidents. An illustration with evaluation of an accidental black spot exercise is presented to demonstrate the data requirements and the application of the method in selecting the rank of accidental black spots. The proposed model is notintended to supplant the work of decision-making teams in ranking the accidental black spot, but rather to help them make qualityevaluations of the available accidental data. One major advantage of the proposed method is that it makes the selection processmore systematic and realistic as the use of fuzzy set theory allows the DMs to express their views on accidental black spot on based on decision criteria in linguistic terms (Very Significant, Significant, and Average, lesssignificant, less significant) rather than as crisp values. So the use of multi criteria decision making is most fitted method for determination of accidental black spot severity index. Occurrence of number of accidents may be reducing with prediction of right model.The purpose of this paper is to develop Accidental Black Spot Severity Index Model (ABSSIM) by usingFuzzy Multiple Criteria Decision Making (FMCDM). The Accidental Black Spots can be, further, ranked through Accidental Black Spot Severity Index Model (ABSSIM) on the basis of their severity.